Clinical analysis of 7 children infected with Talaromyces marneffei - Xie, G (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2022)
Objective: To investigate the clinical manifestations, treatments, and prognosis of pediatric patients with Talaromyces marneffei infection. Methods: In this retrospective study, 7 children diagnosed with Talaromyces marneffei infection in Shenzhen Children's Hospital from July 2017 to October 2021 were recruited. The clinical features, radiology, pathogen detection, immunological evaluation, treatments, and prognosis were analyzed. Results: In 7 cases, 5 were male, 2 were females. The age was from 0.75 to 8.75 years. The main clinical manifestations were fever in 7 cases, cough in 6 cases, malnutrition in 4 cases, papules in 2 cases and medical history of recurrent infection in 3 cases. Physical examination showed that all 7 patients had hepatosplenomegaly, 4 had superficial lymphadenopathy. Laboratory examination showed that 6 cases had decreased hemoglobin and 3 cases had decreased platelet. Chest CT showed that 4 cases had patchy shadows, pleural effusion, mediastinal or axillary lymph node enlargement, 3 had nodular shadows and 2 had cavities. The positive ratio of Talaromyces marneffei culture was 2/2 with tissue samples, 4/5 with bone marrow. The positive ratio was 3/4 by metagenomic next generation sequencing. The fungus was detected in 3 cases by smear microscopy of bone marrow and (or) peripheral blood. All patients were negative for human immunodeficiency virus by the immune function assay. However, 5 cases were confirmed as primary immunodeficiency disease, including 2 cases with high IgM syndrome, 2 with STAT1 gene variation, and the last with severe combined immunodeficiency (IL2RG gene variation). Exclude 1 case which gave up treatment due to acute intracranial infection, and the other patients received effective treatments along with amphotericin B, voriconazole, and itraconazole alone or in combination. Two cases relapsed after medication withdrawal, but 1 case got complete rehabilitation after hematopoietic stem cell transplantation. Conclusions: The clinical manifestations involve multisystem, the common charateristics are fever and cough. The chest CT imaging manifestations are diverse, it should be considered in differentiating tuberculosis. The amphotericin B, voriconazole and itraconazole are effective, but it will easily relapse when withdrawing those antifungal agents